How to write part 1: writing title, abstract, introduction - Asha'ari, Zamzil Amin (2012)
A good title, abstract and introduction is a door to medical publications. These sections are the basis on the first impression for the editors and reviewers, of the article contents. They are also the basis for editorial rejection/filtration in many established journals, and the basis for your article search/citations later after it is published.